Spark plasma texturing (SPT) of p-type [Ca2CoO3]0.62[CoO2] thermoelectric oxide - Noudem, J. G.; Retoux, R.; Lanfredi, S. [UNESP] (Elsevier, 2016)
Hole-doped [Ca2CoO3]0.62[CoO2] (Co349) thermoelectric materials were densified and textured by spark plasma sintering (SPS) process. Thin pre-sintered Co349 lamellar samples were used to process textured monoliths. The textured thin monoliths were further used in obtaining samples with increased thickness for anisotropic property studies by hot-stacking as multiple layers. Infrared measurements were used to investigate the presence of carbon diffused from the SPS tool into the bulk of the sample. The phase compositions, grain texture, as well as microstructure of the samples were analyzed by X-ray diffraction and SEM studies. The high temperature thermoelectric transport properties of the bulk samples and the correlation between the grain orientations, structural and anisotropy of thermoelectric properties were discussed in detail. The textured sample processed by SPT shows the power factor value of 450 μW m-1 K-2 at 600 °C which is 30% higher than the corresponding value for SPS one and eight times larger than samples conventionally sintered.
Keywords: Calcium cobaltate; Grain growth; P-type thermoelectric oxide material; Spark plasma sintering-Texturation